1998
DOI: 10.1002/hep.510280132
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus dynamics in vivo : Effect of ribavirin and interferon alfa on viral turnover

Abstract: Treatment of patients with chronic hepatitis C with recombinant interferon alfa (rIFN-␣) can achieve clearance of the hepatitis C virus (HCV) from serum and liver. However, the overall sustained virological response to IFN-␣ monotherapy is less than 20%. 1,2 Additional clinical trials have been conducted to evaluate alternative treatment modalities in chronic hepatitis C, including therapy with ribavirin. While ribavirin monotherapy revealed no consistent effect on HCV RNA relative to placebo, 3,4 results of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
113
0
3

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(124 citation statements)
references
References 36 publications
(64 reference statements)
8
113
0
3
Order By: Relevance
“…36 Those reports differ from ours in several fundamental ways, including: 1) the clinical characteristics of the cases selected as the subjects; 2) sensitivity and linearity of HCV-RNA quantitation used in the HCV dynamics analysis; and 3) the IFN treatment regimens (doses and intervals). First, while previous studies included virologically heterogeneous patients as the subjects, 36 we selected virologically homogenous cases assessed by viral genotype, baseline viral load, and the number of ISDR mutations in the NS5A region of the HCV genome. In our subjects, no significant difference in the number of ISDR mutations was found among the different treatment groups.…”
Section: Discussionmentioning
confidence: 72%
“…36 Those reports differ from ours in several fundamental ways, including: 1) the clinical characteristics of the cases selected as the subjects; 2) sensitivity and linearity of HCV-RNA quantitation used in the HCV dynamics analysis; and 3) the IFN treatment regimens (doses and intervals). First, while previous studies included virologically heterogeneous patients as the subjects, 36 we selected virologically homogenous cases assessed by viral genotype, baseline viral load, and the number of ISDR mutations in the NS5A region of the HCV genome. In our subjects, no significant difference in the number of ISDR mutations was found among the different treatment groups.…”
Section: Discussionmentioning
confidence: 72%
“…[11][12][13][14][15] Although these studies have undoubtedly provided insight into HCV kinetics, the reported half life (t 1/2 ) of hepatitis C virions has varied greatly among studies. Neumann et al reported the virion t 1/2 to be 2.7 hours, with production and clearance rates of 10 12 virions/day.…”
Section: A Lthough the Impact Of Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…Two early phases of viral elimination were observed with SVR, as previously described for HCV-infected, treated patients: a very early phase with a rapid viral decline, before W4, and a second phase with a slower decline, between W4 and W12 (15,26). In RR, the first phase of decrease was slower than that of SVR and was prolonged up to W12.…”
Section: Discussionmentioning
confidence: 61%
“…In RR, the first phase of decrease was slower than that of SVR and was prolonged up to W12. Indeed, it was shown that the rate of the phase 2 decay correlated closely with that of SVR to IFN-based treatment regimens (26). Especially for NR, a very weak decline was observed before W12.…”
Section: Discussionmentioning
confidence: 93%